علاقة العنف الزواجي بظهور بعض المشكلات السيكوسوسيوتربوية - بوبيدي, لامية (جامعة الوادي - University of Eloued, 2019)
يعد العنف الزواجي من المشكلات الاجتماعية الخطيرة التي تهدد استقرار الأسرة وتماسكها في انعكاس سلبي على وحدة المجتمع ككل. إن مثل هذه العلة الاجتماعية قد تولد عديد المشكلات التوافقية لدى الأعضاء المنتمين إلى هذه الخلية الأسرية، وخاصة الأبناء الذين يتأثرون بما يحدث داخلها. لقد هدفت هذه الدراسة إلى التعرف على العلاقة بين العنف الزواجي بظهور البعض من المشكلات السيكوسوسيوتربوية لدى الأبناء المتمدرسين؛ و لذا تم إجراء دراسة ميدانية تم خلالها تطبيق استبيان ضم (44 بندا) على عينة قصدية قوامها(67 مفردة) مكونة من تلاميذ السنة الثالثة والرابعة بمتوسطة مبارك بولوح بمدينة قالمة. خلصت هذه الدراسة إلى وجود علاقة بين العنف الزواجي وظهور بعض المشكلات النفسية لدى المبحوثين؛ نستدل على ذلك بقيمة المتوسط الحسابي لمجموع الفقرات والمقدرة ب(2.08) وبانحراف معياري (0.72) وبدرجة اتفاق متوسطة. Abstract The conjugal violence is a serious social problem that threatens family stability and cohesion in a negative reflection on the unity of society as a whole. Such a social problem may generate problems of non compatibility among members of this family, especially children who are affected by what happens inside them. This study aimed to identify the relationship between conjugal violence and the appearance of psychosocial and educational problems among the children schooling. To a more understand a empiric study was carried out in which a questionnaire was applicated (44 items) on a sample of (67 individuals) composed of students of the third and fourth year of the medium Mubarak Boulouh in the city of Guelma. This study concluded there was a relationship between conjugal violence and the appearance of some psychosocial and educational problems among the respondents. This result is proved by the value of mean = (2.08) and the standard deviation =(0.72) with the average agreement degree.
لدى الأبناء المتمدرسين في مرحلة التعليم المتوسط
مقال
Keywords: العنف الزواجي، المشكلات السيكوسوسيوتربوية، الابن المتمدرس، العلاقة; The conjugal violence; psychosocial and educational problems; children schooling; relationship